Uncertainty and the Demand for Redistribution - György Molnár; Zsuzsa Kapitány (Hungarian Academy of Sciences, Institute of Economics, 2006)
In this paper we focus on the connection between perception of the competitive pressure situation (unemployment, uncertainty, rising income and wealth inequalities, decreasing mobility) and demand for redistribution. Our context is Hungary, between 2000 and 2002. We identify some basic variables that have important effect on the individuals' preferences for redistribution, namely, uncertainty in actual and future income, and unemployment. Uncertainty raises the demand for redistribution even among the upwardly mobile people, and labour market status is also a major element of dissatisfaction and demand for redistribution. The most frustrated and indecisive people are those who have no clear knowledge about the immediate and the distant future. Indecisive people favour redistribution more than those with negative expectations. Past personal experience and the expectation for future income have a very strong effect on the formation of thinking about income redistribution. Even those who are currently mobile in income tend to support redistribution if they are expecting a decline in their future income and welfare. According to the POUM hypothesis, we also found a negative correlation between expected intergenerational mobility and individual support for redistribution. People perceive their relative income position, their relative mobility and inequality in different ways and their demand for redistribution substantially depends on the subjective and not on the objective income position. Concerning perception of changes in inequality, we found that the more people feel that inequalities are increasing, the more they favour redistribution policies.
Keywords: D31; D63; D80; J62; I31; H50; 330; Mobility; Subjective Mobility; POUM; Subjective Well-being; Redistribution